Pengembangan Aplikasi Virtual Tour Kampus Berbasis XR Menggunakan Unity untuk Meta Quest 2 Dengan Chatbot AI LLaMA - Farhan Maulana; Ni G. A. P. Harry Saptarini; I Putu Astya Prayudha; Gde Brahupadhya Subiksa (Universitas Methodist Indonesia, 2026)
The development of Extended Reality (XR) technology creates new opportunities in delivering more immersive and interactive digital information, particularly in higher education environments. However, current campus promotion media are still dominated by static visual presentations and have not been able to provide natural two-way interaction for users. This study aims to develop an XR-based campus virtual tour application using Unity for the Meta Quest 2 device integrated with an Artificial Intelligence chatbot based on the Large Language Model (LLaMA). The application enables users to explore the campus environment in a three-dimensional virtual space, interact with campus objects, and ask questions through voice input to obtain real-time responses. The research method used is Research and Development (R&D) with an experimental software engineering approach and Agile iterative incremental development model. System development includes XR environment implementation, speech-to-text integration, prompt delivery to the LLaMA model through REST API using LM Studio as a self-hosted AI server, and text-to-speech response generation. System evaluation was conducted using black box testing, performance testing on AI response latency and frame rate stability, and usability evaluation using the User Acceptance Testing (UAT). The expected result of this research is an interactive, stable, and responsive campus virtual tour application capable of providing a more immersive information experience while functioning as an independent digital promotion medium without dependence on cloud-based AI services.